The path to mass evil : Hannah Arendt and totalitarianism today - Hardiman, Michael (Routledge, 2023)
Philosophical approaches to the problem of evil -- The banality of evil -- Banality and the masses -- Ideology, totalitarianism and mass evil -- Pernicious ideologies -- Totalising ideology and religion -- The fusion of ideology with banality -- The murderous alphabet -- Combatting mass evil : Arendt's legacy today.